Role of human HSPE1 for OPA1 processing independent of HSPD1 - Nelson Yeung; Daisuke Murata; Miho Iijima; Hiromi Sesaki (iScience, 2023)
Summary: The human mtHSP60/HSPD1-mtHSP10/HSPE1 system prevents protein misfolding and maintains proteostasis in the mitochondrial matrix. Altered activities of this chaperonin system have been implicated in human diseases, such as cancer and neurodegeneration. However, how defects in HSPD1 and HSPE1 affect mitochondrial structure and dynamics remains elusive. In the current study, we address this fundamental question in a human cell line, HEK293T. We found that the depletion of HSPD1 or HSPE1 results in fragmentation of mitochondria, suggesting a decrease in mitochondrial fusion. Supporting this notion, HSPE1 depletion led to proteolytic inactivation of OPA1, a dynamin-related GTPase that fuses the mitochondrial membrane. This OPA1 inactivation was mediated by a stress-activated metalloprotease, OMA1. In contrast, HSPD1 depletion did not induce OMA1 activation or OPA1 cleavage. These data suggest that HSPE1 controls mitochondrial morphology through a mechanism separate from its chaperonin activity.